Audit of vancomycin TDM in ECMO patients. Issue 6 (1st February 2011) - Wheeler, S K; Martinet, S; Mulla, H
Abstract : Objective: The aim of this investigation was to evaluate current vancomycin dosing schedules and TDM in patients on ECMO at Glenfield Hospital following the introduction of a new ECMO circuit. Specifically the objectives were: ▶ to collect trough plasma vancomycin levels and associated dosing regimens ▶ to assess the proportion of patients that achieve target trough levels ▶ to suggest improvements to current dosing/TDM approaches. Methods: ECMO patients treated at Glenfield Hospital from April 2007 onwards were identified from an ECMO database and study data were gathered retrospectively from medical notes, prescription charts and the hospital microbiology/biochemistry database. Data collected included, patient demography, doses, plasma vancomycin levels, urea and creatinine, and if relevant duration of continuous veno-venous hemofiltration (CVVH) support. Descriptive statistics were used to analyse the data. Data were stratified into age groups (neonate (<4 weeks), infant (1–12 months), children (1–18 years) and adults (>18 years)) to enable comparisons between groups to identify whether this affected the dosing schedule. Therapeutic trough levels were defined as 10–20 mg/l although UHL define a therapeutic trough as 5–15 mg/l. Vancomycin schedules currently are 10 mg/kg TDS in paediatrics and 1 g BD in adults. Doses and/or frequency are reduced in severe renal impairment and CVVH, but there is no dose adjustment for ECMO. Results: 32 patients were included in the audit (10 neonates, 4 infants, 5 children and 13 adults) and 223 plasma vancomycin levels were assessed (30 neonates, 145 infants, 18 children and 30 adults). 9 patients received CVVH support. Plasma trough levels ranged from 2.0 to 31.7 mg/l. Preliminary analysis of the results suggests that when using the range of 10–20 mg/l for neonates 27% of trough levels are subtherapeutic (defined as <10 mg/l) and 16% are toxic (defined as >20 mg/l). In infants 44% of troughs were subtherapeutic and 4% were toxic whereas in children 73% were subtherapeutic and 10% were toxic. In adults there were 38% of troughs subtherapeutic and 4% toxic. If we analyse the results against the hospitals recommended range of 5–15 mg/l for neonates 4% of trough levels are subtherapeutic (defined as <5 mg/l) and 40% are toxic (defined as >15 mg/l). In infants 9% of troughs were subtherapeutic and 22% were toxic whereas in children 42% were subtherapeutic and 10% were toxic. In adults there were 15% of troughs subtherapeutic and 19% toxic. The analysis is ongoing and it is hoped that a pharmacokinetic modelling approach will provide further insight. Conclusion: The preliminary results show that vancomycin levels in a large proportion of ECMO patients were outside the therapeutic range. The results fall mostly into the 5–15 mg/l range which is too low for critically ill patients. Following this we need to clarify that the ITU/ECMO patients have a higher range and doses should not be reduced unless levels are >20 mg/l. This should provide a more effective dose of vancomycin to treat sepsis in these critically ill patients without being concerned about nephrotoxicity.